Spiritual Development in Social Context: The Role of Christian Psychotherapy in the Formation of Identity - Ilievski, Naum; Angelina Ilievska (European Journal of Multidisciplinary Studies, 2018)
Spiritual growth and development enable complete self-actualization. In the three stages of spiritual development – described in Christian psychotherapy and based on a practical spiritual life established in Christian patrology – man from an individual becomes a person. He builds his identity during this process. The main goal of this paper is to represent the practical aspect of spiritual Christian life and its impact in a social context. In addition, it offers a representation of the spiritual development process – a model in Christian psychotherapy, as well as a description of each stage at which spiritual identity is formed. It is a descriptive paper where the basic methods of this process are elaborated: establishing a personal relationship with a spiritual father – psychotherapist, implementing the FCP and metanoia. Analysis of identity is made by utilizing two dimensions: personal and social one. The concept of personality is profoundly connected with the ego, identity, self and identification. Identification outside of the Divine Person with partial forms of existence leads to individual and social splitting, and polarization of particles. Building a spiritual identity enables formation of personality that exists out of their spiritual self and builds a pastoral relationship in all life areas: personal, family and social. A spiritually realized person – out of the borders of individual script – is socially useful, creative and functional in the wider social context.